Investigating adaptation to environmental variability in forest trees through molecular phylogenetic analysis - Cesare Garosi; Cristina Vettori; Roberta Ferrante; Donatella Paffetti (PLoS ONE, 2025)
We conducted a molecular phylogenetic analysis of the abiotic stress response in 13 key European forest species ( Fagus sylvatica L., Quercus robur L., Quercus ilex L., Quercus pubescens Willd., Quercus suber L., Quercus lobata L., Juglans regia L., Populus trichocarpa L., Pinus taeda L., Pinus nigra J.F. Arnold, Pinus pinea L., Pinus pinaster Aiton and Abies alba Mill.) to clarify how different abiotic stressors have influenced their adaptation. The study on the evolution of abiotic stress responses in these species, seeks to uncover the factors driving their distinct evolutionary pathways of adaptation. We created the dataset by collecting data from genomic dataset on genes relevant to the response to abiotic stress in the target species dataset. Then, we used the data in the dataset to search for possible orthologs in the studied species dataset. A matrix was created with sequences of each identified ortho-group, closely related to the analyzed genes, and phylogenetic relationships were reconstructed using the maximum likelihood (ML) method. Pairwise estimates of synonymous and nonsynonymous substitutions per site (Ks and Ka, respectively) were calculated using the ML method. Analysis of 616 genes associated with abiotic stress response revealed 347 genes in angiosperms species, with F. sylvatica having the highest count, and 269 genes in conifers, where A. alba contributing the most. Drought stress exhibited the highest number of shared genes, while freezing stress showed the least. Substitution rate analysis indicated higher average values in angiosperms species, with a stronger signature of adaptive evolution in conifers, as suggested by the higher Ka/Ks ratio. The study unveils distinctive patterns in the evolutionary dynamics of molecular responses to abiotic stresses between the 13 key forest tree species. Lower substitution rates in conifers suggest unique constraints, likely influenced by larger genomes and ancient lineage divergence. The prevalence of Ka/Ks values below unity emphasizes strong selective constraints, highlighting the conservation of abiotic stress response mechanisms across diverse lineages.